FAKTOR-FAKTOR YANG MEMENGARUHI KESULITAN PEMAHAMAN BACAAN: STUDI KASUS PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Siti Ina Tenripada; Bhakti Pandi Hasin; Karmila Indah Hasin (Fakultas Teknik Universitas Negeri Makassar, 2026)
This study aims to analyze students’ difficulties in comprehending reading texts and to identify the factors influencing these difficulties among fifth-grade elementary school students. The study employed a qualitative approach using a case study design conducted at SD Inpres Malengkeri Bertingkat Makassar. The participants consisted of 30 students and one classroom teacher, with six students selected as interview informants through purposive sampling based on variations in reading ability. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the qualitative data analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that students’ reading comprehension difficulties are primarily related to three aspects: understanding the content of the text, identifying main ideas, and interpreting vocabulary. These difficulties are influenced by limited vocabulary mastery, low reading interest, and instructional practices that still emphasize mechanical reading rather than comprehension. Therefore, reading instruction should be designed to be more interactive, contextual, and meaning-oriented to enhance students’ reading comprehension skills.